(untitled) (Scripta : English Department Journal, 2026)
This study aims to find out the teachers’ perceptions of word-matching game-based English vocabulary instruction for students with hearing impairments in a Special School (SLB) in Medan, North Sumatra, Indonesia. Data were collected through semi-structured interviews, field notes, and document analysis with one experienced English teacher using a qualitative case study design. The findings revealed four primary themes related to perceived effectiveness: visual alignment with students’ learning styles, increased motivation and enthusiasm, improved vocabulary retention, and fostering peer interaction and collaboration. The teacher also mentioned four problems of implementation: the difficulty of understanding the initial instruction, the management of students’ attention and focus, the difference in students’ capability, and the extensive preparation of materials and facility’s support.These findings provide evidence that the word matching game is an extremely effective, visually-based vocabulary strategy that meets the learning needs of students with hearing impairment, while also revealing the need for systemic institutional support for its sustainable implementation.